CHALLENGES AND SOLUTIONS FOR TRANSLATING IDIOMATIC EXPRESSIONS (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
Translating idiomatic expressions requires navigating linguistic, cultural, and contextual barriers to maintain the intended meaning and impact. This article identifies key challenges, such as cultural specificity, lack of direct equivalents, and ambiguity, while offering solutions that emphasize creative adaptation and cultural sensitivity. Translators are encouraged to balance fidelity to the source language with clarity and relatability in the target language. By leveraging contextual understanding, collaborative input, and translation tools, idiomatic expressions can be effectively rendered to resonate with diverse audiences.